Computational and spectroscopic studies of new rhenium(I) complexes containing pyridylimidazo[1,5-a]pyridine ligands: Charge transfer and dual emission by fine-tuning of excited states - Salassa, Luca; Garino, Claudio; Albertino, Andrea; Volpi, Giorgio; Nervi, Carlo; Gobetto, Roberto; Hardcastle, Kenneth I. (Organometallics, 2008)
Three new Re(CO)(3)Cl complexes (ReL1-ReL3) containing the N,N-bidentate ligands 1-(2-pyridyl)-3-phenylimidazo[1,5-a]pyridine (L1), 1-(2-pyridyl)-3-(4-tert-butylphenyl)imidazo[1,5-a]pyridine (L2), and 1-(2-pyridyl)-3-(4-dimethylaniinophenyl)imidazo[1,5-a]pyridine (L3) were synthetized and fully characterized. Photophysical properties of L1-L3 and ReL1-ReL3 were studied with absorption and emission spectroscopy. The X-ray structure of ReL3 was determined. Time-dependent DFT (TDDFT) calculations were performed in order to elucidate the electronic structures and the excited states of ligands and complexes. Ligands L1 and L2 show (1)pi-pi* emission with limited charge-transfer character (CT), while L3 emits from an excited state with higher CT character due to the presence of a dimethylamino group. No emissive metal-to-ligand charge-transfer (MLCT) states are found for the rhenium complexes. ReL1 and ReL2, although similar to their ligands, display a ligand-centered (1)pi-pi*/(3)pi-pi* dual emission; singlet emissions fall at 21.8 x 10(3) (458 nm) and 22.6 x 10(3) cm(-1) (443 nm), respectively, and the structured triplet emissions have two peaks at 17.9 x 10(3) (558 nm) and 16.3 x 10(3) cm(-1) (613 nm) in both complexes. ReL3 emits from a ligand-centered CT state at 18.9 x 10(3) cm(-1) (530 nm). Finally, the complex [Re(L1)(CO)(3)py]PF6 (ReL1py) (where py = pyridine) was prepared and studied by spectroscopy and computational methods. The complex has high-energy emission centered at 22.9 x 10(3) cm(-1) (437 nm). DFT calculations show that dual fluorescence almost disappears due to the reduced spin-orbit coupling. Finally, electrochemical properties of ligands and rhenium complexes have been investigated.